2012
DOI: 10.1007/s00246-012-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Dexmedetomidine in Children With Heart Failure

Abstract: This retrospective observational study aimed to evaluate the safety and efficacy of dexmedetomidine (DEX) for children with heart failure. The study was conducted in the cardiovascular intensive care unit (CVICU) of a single, tertiary care, academic children's hospital. A retrospective review of the charts for all children (up to 18 years of age) with signs and symptoms consistent with congestive heart failure who received DEX in our CVICU between April 2006 and April 2011 was performed. The patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…No study has compared Dexmedetomidine and Midazolam to provide sedition in children for performing CT. No significant difference was observed between the effects of these drugs in providing sedition for patients referring to the ICU which is compatible with the findings of the current study. In the study which has compared the effect of Dexmedetomidine and Midazolam on patients undergoing cataract surgery, Dexmedetomidine showed no preferences over Midazolam and has the same performance which is compatible with the results of the present study (7,8,9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No study has compared Dexmedetomidine and Midazolam to provide sedition in children for performing CT. No significant difference was observed between the effects of these drugs in providing sedition for patients referring to the ICU which is compatible with the findings of the current study. In the study which has compared the effect of Dexmedetomidine and Midazolam on patients undergoing cataract surgery, Dexmedetomidine showed no preferences over Midazolam and has the same performance which is compatible with the results of the present study (7,8,9).…”
Section: Discussionsupporting
confidence: 90%
“…Drugs used so far to provide sedation in children are Cholorohydrates and Pentobarbitals. These drugs have long-term effect which causes increase of the recovery time and level of side effects (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…In a small, retrospective, observation study of children with HF, dexmedetomidine did not affect heart rate, mean arterial pressure, or inotrope score at the termination of infusion; however, 2 patients had a 50% decrease in mean arterial pressure and 1 patient had a 50% decrease in heart rate compared with baseline in the first 3 hours of infusion. 30 In neurocritical care patients, dexmedetomidine exhibited similar incidences of severe hypotension (mean arterial pressure <60 mm Hg) and bradycardia (heart rate <50 bpm) compared with propofol. 31 …”
Section: Inhalational or Volatile Anestheticsmentioning
confidence: 92%
“…48 Other studies showed that the use of dexmedetomidine is safe in patients with congenital heart diseases and in the post-operatory of cardiac surgery without hypotension and bradycardia harmful to the patient. [49][50][51][52][53] Management of abstinence syndrome Prolonged administration of opioids and/or benzodiazepines leads to tolerance. Rapid suspension of these medications implicates a myriad of signs and symptoms, called abstinence syndrome.…”
Section: Resultsmentioning
confidence: 99%